Relationship between Self-efficacy and Mental Health with Health Literacy in Patients with Diabetes in Kazerun City, Shiraz, Iran - Mohammad Taghi Sohrabi renani; Fahimeh Nourafkan; Fariba FathiMard; Kaveh Sadegheyan khashoei; roghayeh Mazarei (Shahid Sadoughi University of Medical Sciences, 2020)
IntroductionSince diabetes is a complex network of psychological and healthcare factors, this paper aims to investigate the relation between type 2 diabetes and mental health Method: This study was analytical cross-sectional research on 60 diabetic patients referring to Kazerun health care centers, southwest of Iran, in 2018. The samples were selected by convenience sampling method. The data were collected using the Demographic Profile Questionnaire, General Self-Efficacy Scale  (GSES), Health Literacy Questionnaire  (HELA), and Mental Health Continuum (MHC-SF). Data analysis was performed in APSS v21 and from descriptive statistics including mean and standard deviation and using the statistical tests of Spearman correlation coefficient and multiple regression analysis (P <0.01). Findings:   Mental health has a significant positive relationship with health literacy (p <0.001). Thus, individuals with better mental health evaluate their level of health literacy better. However, no relationship was found between self-efficacy and health literacy(r= -0.19, p >0.001). Besides, regression results indicated that mental health can predict a 54% variance of health literacy (R2= 0.54, p <0.001). Conclusion: The findings of this study shows that boosting an individual's mental health leads to an increase in health awareness in patients afflicted with diabetes which after all, can cause a better coping capability in these people.